(3faGFS GdEcQGe aj aJhM HdO Gddg GdMQGes - (3GdeQRhbj , Rjf GdYGHOjf eMeO Hf eOjf Hf CHj GdYHGS GdeQRhbj, GdeQRhbj,J (B1060 (3g` s
(3ChdgG (B:s
(3hHYO , abO JTfa SeYi HJUaM gPG GdLGeY GdQMjH, hGdeTQY GdYLjH s
(3BNQgG (B:s
(3hcPG GdChd hGdUMGH LejYG eGHOG HOQ GdceGd hJeG s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B94 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B196s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B456 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs